Imperial Ideology and Architecture - Yaghi, Ghazwan, (Leiden Studies in Islam and Society ;, 2024)
The goals and tactics of a state's ruling elite influence its artistic and architectural output, shaping the overall characteristics, orientation, and themes of its creations. Architecture reflects political ideology and historical events, showcasing the power and cultural values of the state, with implications for politics and authority. This book presents a comprehensive and nuanced exploration of the intricate interplay between art, politics, and religion within the architectural legacy of Mamluk Damascus. It sheds light on how these dynamics enrich our comprehension of the past and contribute to contemporary dialogues concerning the preservation of cultural heritage.